If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 5(2r + -6) = -107 Reorder the terms: -7 + 5(-6 + 2r) = -107 -7 + (-6 * 5 + 2r * 5) = -107 -7 + (-30 + 10r) = -107 Combine like terms: -7 + -30 = -37 -37 + 10r = -107 Solving -37 + 10r = -107 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '37' to each side of the equation. -37 + 37 + 10r = -107 + 37 Combine like terms: -37 + 37 = 0 0 + 10r = -107 + 37 10r = -107 + 37 Combine like terms: -107 + 37 = -70 10r = -70 Divide each side by '10'. r = -7 Simplifying r = -7
| 5(3x+9)(5x-15)=0 | | (x-4)(x+1)=14 | | e^9x=3 | | 5(1+3b)+7(7-3b)=30 | | -5p+-4(-p+4)= | | 8-11=-13 | | -7x-3=-38 | | y*86=259 | | -5y+3z=12 | | -4(8+7h)+2= | | 9x+9=3y+6 | | 9+9x=6+3y | | 3ab-ab= | | 2x-=3 | | 3y+6=9x+9 | | -9(-9+3j)= | | 6x+y+8x+2y=180 | | -2(a+1)-3(1-7a)=-24 | | 6x+y+8x+2y=0 | | 2x+4x+6x-2(x+3)=34 | | 6(2j+1)+7= | | 8+4x=5x+4 | | -1+5(x+2)=12x+3-17x | | X+3x+2x+3(x+1)=30 | | 5-16=8.5 | | 3x-6y+9= | | 3(4+10x)+x= | | 8x+4x=5x+4 | | x^4-4x^3-x^2+16x=0 | | 2x-3(-5x+8)=17x-2+8 | | 5(a+4)-6a+1=12 | | -8(y+2)-16=16 |